Technical and Economical Evaluation of Micro-Solar PV/Diesel Hybrid Generation System for Small Demand - Tsutomu Dei; Nomuulin Batjargal (International Journal of Renewable Energy Development, 2022)
This paper is intended as an investigation on a reliability of solar PV(Photovoltaic) and DG (Diesel Generator) hybrid system and the economical evaluation. In the remote area or island countries, diesel generator is a common technology for supplying power. In general, the price of diesel oil is expensive in remote areas. Therefore, introduction of the technologies which can reduce the fuel consumption for power generation is important in those area. Interconnection of solar PV with isolated diesel distribution lines is one of the options when expanding power generation facilities. However, the output of solar PV is influenced by the weather condition, it is difficult to ensure a constant output and control power amount. Using unstable input for power generation such as solar PV increases the risk of power outage due to instability of system voltage and frequency fluctuations. In this study, experiments were conducted to clarify the unstable condition using the micro-solar diesel hybrid system using solar PV (2kW), Battery Bank (24V,420Ah) and Diesel Generator (4.7kVA) and load(1500W) at Ashikaga University (AU). The experiments are conducted by two different setups, a hybrid system of solar PV and DG and the hybrid with battery bank.  The results of the experiments show the frequency fluctuations becomes smaller by the hybrid system with battery bank. And the mechanical governor which attached to the DG has important function to stabilize frequency fluctuation. In the study, economic viability of the solar PV and DG hybrid system is examined by computing the Internal Rate of Return (IRR). In the calculation of the least-cost alternative system, a diesel engine powered generation system with the capacity to generate the same amount of electricity as the solar PV-DG hybrid system was used. The IRRs of the solar PV – diesel hybrid system is positive in all configuration. IRR becomes larger in the hybrid system without a battery bank and also it becomes larger with increase of the penetration ratio of solar PV. The configuration of solar PV and DG hybrid system have to be considered by the type of power demand. If the demand user requires quality power such as stabilized voltage and frequency in minimum range, battery bank have to be installed to the system. If the economical operation by saving the amount of fuel consumption is more important, battery bank does not need to be included. The system is feasible on the both aspect of technical and economical, therefore it can be introduced as reliable energy supply system for small power demand in remote areas.